Advances in Integrated Traditional Chinese and Western Medicine for Prevention and Treatment of Arteriovenous Fistula Thrombosis in Maintenance Hemodialysis Patients - Zhao, Siyang; Fang, Wenjuan; Zhao, Yazhou; Li, Na (Journal of Contemporary Medical Practice, 2026)
Autologous arteriovenous fistula (AVF) is the preferred permanent vascular access for maintenance hemodialysis (MHD) patients. Thrombosis is the leading critical complication causing AVF failure. Western medical interventions, including thrombolysis, endovascular procedures, and surgery, can rapidly restore blood flow in the acute phase but are associated with high rates of long-term restenosis and recurrent thrombosis. In traditional Chinese medicine (TCM), AVF thrombosis falls into the categories of “Mai Bi” (vessel impediment) and “Xue Bi” (blood impediment), with “qi deficiency and blood stasis” as the core pathogenesis throughout the entire disease course. TCM therapies, including oral herbal medicine, external fumigation, washing/soaking and wet compresses, moxibustion, massage, and rehabilitation exercises, can systematically improve the uremic hypercoagulable state, protect vascular endothelium, and maintain local microcirculatory homeostasis. Currently, integrated Chinese-Western medicine has evolved from simple superposition to a “stage-stratified, complementary advantages” model, i.e., Western medicine-dominated rapid recanalization in the acute phase, synergistic Chinese-Western intervention against restenosis in the recovery phase, and TCM-dominated long-term maintenance in the stable phase. This article systematically reviews the pathogenesis, therapeutic advances, and stratified management strategies for AVF thrombosis in end-stage renal disease (ESRD) patients, aiming to provide evidence-based references for standardized clinical prevention and treatment.